2002
DOI: 10.1088/0022-3727/35/20/311
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of thermoluminescent glow peaks of CaF2: Dy (TLD-200) after  -irradiation

Abstract: Variable dose (VD), T m-T stop , initial rise (IR), variable heating rate (VHR), peak shape (PS) and computerized glow curve deconvolution (CGCD) methods are used to determine the number of peaks, the order of kinetics (b), the activation energy (E a) and attempt-to-escape frequency (s) associated with the glow peaks in CaF 2 : Dy (TLD-200) after β-irradiation between the dose level 0.1 and 110 Gy. The T m-T stop procedure indicates that the glow curve of this crystal consists of at least nine glow peaks. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 21 publications
1
29
1
1
Order By: Relevance
“…Previously published studies have shown that determination of activation energy and frequency factor mainly depends on the prior knowledge of kinetic order and the exact number of glow peaks in the glow curve [7][8][9]. Therefore, to form an opinion about the number of glow peaks and kinetic orders of all individual glow peaks in the glow curve structure of Al-doped LiB 3 O 5 , the additive dose method was firstly utilized in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published studies have shown that determination of activation energy and frequency factor mainly depends on the prior knowledge of kinetic order and the exact number of glow peaks in the glow curve [7][8][9]. Therefore, to form an opinion about the number of glow peaks and kinetic orders of all individual glow peaks in the glow curve structure of Al-doped LiB 3 O 5 , the additive dose method was firstly utilized in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, if the previous history of the material is unknown, it is advantageous to anneal the sample at 400°C for 30 min before putting it to any dosimetric use. Previously published studies have shown that the determination of E a and s mainly depends on the prior knowledge of kinetic order (b) and the exact number of glow peaks in the glow curve [19][20][21][22][23]. The investigations were based on the principle of different characteristic response patterns of glow peaks during irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in our previously published study [14], it is essential to find the kinetic order (b) and exact number of the glow peaks in each glow curve before the evaluating of trap depth (activation energy E a ) and frequency factor (s). Therefore, to find the b-values of each individual glow peak, the additive dose method was firstly used.…”
Section: Resultsmentioning
confidence: 99%